Hematopoietic Stem Cell Transplantation for the Pediatric Hematologist/Oncologist (Springer International Publishing, 2018)
This volume provides a comprehensive and state-of-the-art review on pediatric hematopoietic stem cell transplantation (HSCT). The book covers such topics as graft versus host disease (GVHD), HSC mobilization, stem cell selection, and HSCT-relevant laboratory assays and techniques. The text is specially formatted so that the scientific basis of HSCT and ethical considerations are integrated into the relevant clinical framework. Each chapter also includes diagrams, illustrations, and tables that summarize key points and concepts that can be used as a quick visual reference for the reader. Written by experts in the field, Hematopoietic Stem Cell Transplantation for the Pediatric Hematologist/Oncologist is a valuable resource on pediatric HSCT suited for pediatric hematologists-oncologists, fellows, advanced practitioners, clinical nurses, and other referring physicians.